Train drain? Access to skilled foreign workers and firms’ provision of training - Oswald-Egg, Maria Esther [Verfasser]; Siegenthaler, Michael [Verfasser] (My University, 2021)
“Does better access to skilled workers reduce firms’ willingness to provide general skills training to unskilled workers? We analyze how the gradual opening of the Swiss labor market to workers from the European Union affected the number of apprenticeship positions that firms provide. We exploit that the availability of skilled workers increased more in firms close to the border because they gained unrestricted access to cross-border workers from neighboring countries. Our Difference-in-Differences estimates suggest that firm-provided training and access to skilled workers are not necessarily substitutes: opening the borders did not have a statistically significant effect on apprenticeship provision. We show theoretically and empirically that the small impact was the consequence of two opposing effects: the greater availability of skilled workers reduced firms’ incentive to train because the cost of hiring external labor fell. Positive impacts on firm growth worked in the opposite direction.“ (authors’ abstract; BIBB-Doku)
Keywords: S 3.2 Unternehmen und Behörden; 370; 330; Fachkräfte; Arbeitsmigration; ausländischer Arbeitnehmer; Einflussfaktor; Ausbildungsverhalten; Betrieb; Ausbildungsbereitschaft; Grenzgebiet; Schweiz